Perhubungan awam dan perpustakaan / Norasiah Hj Harun - Hj Harun, Norasiah (Faculty of Information Management, 2015)
The importance of Public Relations for libraries and librarians in Malaysia is discussed. The article describes the importance of Public Relations in enhancing the image of libraries and librarians. The method on how to undertake Public Relations program is discussed.